Campylobacter jejuni Cytolethal Distending Toxin C Exploits Lipid Rafts to Mitigate Helicobacter pylori-Induced Pathogenesis - Yeh, Jia-Yin; Lin, Hwai-Jeng; Kuo, Chia-Jung; Feng, Chun-Lung; Chou, Chia-Huei; Lin, Chia-Der; Wu, Hui-Yu; Li, Chen-Yi; Chiu, Cheng-Hsun; Lai, Chih-Ho (Frontiers in Cell and Developmental Biology, 2021)
Helicobacter pylori infection is associated with several gastrointestinal diseases, including gastritis, peptic ulcer, and gastrointestinal adenocarcinoma. Two major cytotoxins, vacuolating cytotoxin A (VacA) and cytotoxin-associated gene A (CagA), interact closely with lipid rafts, contributing to H. pylori-associated disease progression. Campylobacter jejuni cytolethal distending toxin (CDT) consists of three subunits: CdtA, CdtB, and CdtC. Amongst, CdtA and CdtC bind to membrane lipid rafts, which is crucial for CdtB entry into cells. In this study, we employed recombinant CdtC (rCdtC) to antagonize the functions of H. pylori cytotoxin in cells. Our results showed that rCdtC alleviates cell vacuolation induced by H. pylori VacA. Furthermore, rCdtC reduces H. pylori CagA translocation, which decreases nuclear factor kappa-B (NF-κB) activation and interleukin-8 (IL-8) production, resulting in the mitigation of gastric epithelial cell inflammation. These results reveal that CdtC hijacks cholesterol to compete for H. pylori cytotoxin actions via lipid rafts, ameliorating H. pylori-induced pathogenesis.